Agricultural Credit Guarantee Scheme Fund (Nigeria) : annual report and statement of accounts for the year ended 31st December, 1981 - Agricultural Credit Guarantee Scheme Fund (Nigeria).; Central Bank of Nigeria (Lagos, Nigeria : Central Bank of Nigeria, 1981)
This is the annual report and statement of accounts of the Agricultural Credit Guarantee Scheme Fund (Nigeria) for the year ended 31st December, 1981.
lje 04/03/2019
Arch
Keywords: Agricultural credit; Loans; Nigeria